The Development of Global Software Outsourcing and Its Project Issues in a Leading UK Financial Company - Zhou, Ji; Mayhew, Pam J (2009 First International Conference on Information Science and Engineering, 2009)
Global Software Outsourcing (GSO) is a very topical and emotive subject which lacks project level research. Although most of the UK's large scale companies are employing GSO presently, its performance does not entirely satisfy the industry's expectations. This paper explores the development of GSO and its growth in the UK. A case study has been carried out to explore the project issues in a leading UK financial company. Industry observation and interviews have been introduced to collect the industrial data. Based on the data analysis, some representative project issues and their implications are outlined - resource, communications, project sponsors, requirements, and the project process critically influence the success of GSO projects in the company. The last part of this paper describes some possible resolutions to the problems identified.